Monitoring the spatial distribution pattern according to urban land use and health risk assessment on potential toxic metal contamination via street dust in Ankara, Türkiye - Isinkaralar, Oznur; Isinkaralar, Kaan; Bayraktar, Emine Pirinç (Springer Science and Business Media LLC, 2023)
The urbanization processes with growing vehicle numbers cause heavy metal pollution in street dust, and high populations in metropolitan cities are exposed to pollutants. This paper aims to monitor the spatial distribution of heavy metals and evaluate the concentrations via health risk assessment of HMs (Cu, Ni, Cd, Co, Pb, and Zn) that expose the inhabitants to health hazards. According to the results of the current study, sixty street dust samples were applied to the acid digestion technique and quantification by inductively coupled plasma-mass spectrometry (ICP-MS). The spatial distribution of the selected heavy metals in the street dust was investigated using the spatial analysis tool in ArcGIS 10.0 according to population density and land use. In the present study, we used hazard index and cancer risk methods to estimate the public health risk of the pollutants exposed to street dust in Ankara. The concentrations range of the elements in street dust over the study area ranged from 3.34-4.50, 31.69-42.87, 16.09-21.54, 42.85-57.55, 0.00-3.51, and 23.03-30.79, respectively. The overall decreasing order of mean concentration of metals was observed as follows: Pb > Cu > Ni > Co > Cd > Zn. Vehicle traffic and industrial activities seem to be the most critical anthropogenic sources responsible for dust pollution in the study area. The risk assessment of Pb and Ni exposure was the highest, and the hazard index values were 2.42E + 00 and 2.28E + 00 mg/kg/day for children. However, the effect on adults was 2.62E-01 and 2.37E-02 mg/kg/day, followed by inhalation and dermal contact with street dust was almost negligible. The decreasing concentration is modeled spatially along the western development corridor of the city. The risk to public health is high in areas with high densities close to the city center and the main artery.
Keywords: Adult; Dust; Risk Assessment; Heavy Metal Poisoning; Lead; Humans; Environmental Pollutants; Child; Cadmium; Environmental Monitoring; 6. Clean water; 3. Good health; 12. Responsible consumption; 13. Climate action; 11. Sustainability